ANALISIS PROSEDUR AUDIT KAS DAN SETARA KAS PADA PT ABC OLEH KAP BUNTARAN & LISAWATI - Pramesti, Sri Dilla; Azmiyanti, Rizdina (LPPM Universitas Bina Bangsa, 2024)
Audit of cash and cash equivalents is a procedure used to examine the fairness of the presentation of cash and cash equivalents balances in the company's financial statements. This study aims to determine whether the audit procedures carried out by KAP Buntaran & Lisawati at PT ABC are in accordance with generally accepted standard audit procedures for cash and cash equivalents. The research method used is descriptive qualitative research method by presenting conclusions or results from the data collected based on a theoretical concept. The results showed the procedures carried out by KAP Buntaran & Lisawati auditors during the examination of cash and cash equivalents at PT ABC. The conclusion of this study is that the inspection procedures for cash and cash equivalents carried out by KAP Buntaran & Lisawati auditors are in accordance with generally accepted procedural standards, so that auditors are expected to be able to detect material misstatements during the audit of PT ABC